Organic solar cells with 2-Thenylmercaptan/AU self-assembly film as buffer layer - Zhang, Shiyong; Chen, Zhijian; Xiao, Lixin; Qu, Bo; Qihuang Gong (SOLAR ENERGY MATERIALS AND SOLAR CELLS, 2011)
The interface between an electrode and the organic active layer is an important factor in organic solar cells (OSCs) that influences the power conversion efficiency (PCE). In this report, a buffer layer of 2-thenylmercaptan/Au self-assembly film is introduced into OSCs as a substitute for the poly(3,4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT: PSS) layer. The electrode/active layer interface is meliorated by Au-S coordinate bond of self assembly after applying this buffer layer. The series resistance reduces from 20 Omega cm(2) in a device based on PEDOT:PSS to 10.2 Omega cm(2). Correspondingly, the fill factor (FF) increases from 0.50 to 0.64. Moreover, due to the dipole of this self-assembled layer, the open circuit voltage (V-oc) also increases slightly from 0.54 V to 0.56 V and the PCE reaches 2.5%. (C) 2010 Elsevier B.V. All rights reserved.